ANALISIS PENGUNGKAPAN LAPORAN KEBERLANJUTAN PT BANK NEGARA INDONESIA (Persero), Tbk. TAHUN 2023 BERLANDASKAN STANDAR GRI TAHUN 2021 - Mubaroq, Afiq Chamim; Pramuka, Bambang Agus (Business, Accounting and Management Journal, 2024)
Sustainability reports are a form of company commitment to implementing sustainability in their company. Various sustainability concepts and theories inspired the birth of sustainability. GRI is a guide for companies to report their activities related to social, economic and environmental matters. This research uses descriptive methods to explain the history, philosophy and implementation of GRI in sustainability reports. The sample used in the research is the sustainability report of PT Bank Negara Indonesia (Persero), Tbk in 2023. The research results explain the philosophy of financial reporting based on transparency, trustworthiness, relevance, comparability and integrity. Meanwhile, the philosophy of sustainability reporting is based on transparency, stakeholder involvement, consistency, innovation and continuous improvement. According to the Koran and hadith, the philosophy of sustainability reporting can be found in concepts that emphasize the importance of social justice, environmental responsibility and general welfare. In 2023, BNI has fulfilled 89.3% of all points in the 2021 GRI. In addition, BNI has also fulfilled the pentuple bottom line aspects, namely profit, people, planet, prophet and phenotechnology.